ANALISIS STRUKTUR, KONSENTRASI, DAN EFISIENSI PASAR INDUSTRI TELEKOMUNIKASI DI INDONESIA - Zulfikar Adi Satria; Tri Kunawangsih P (Media Ekonomi, 2016)
The purpose of this study was to determine how the structure, market concentration and efficiency of the telecommunication industry in Indonesia. The analysis technique used in this research is Concentration Ratio (CR4) and Data Envelopment Analysis (DEA). Total revenue of the Indonesia telecommunication industry from 2010-2015 were used to calculate Concentration Ratio (CR4) and Data Envelopment Analysis (DEA) are input and output, the input consists of total assets, debt and equity, the output consists of total revenue and gross profits. Based on the analysis results of Concentration Ratio (CR4) is quite of very high ranging from 98,17% - 99,67%, the market structure in property industry classified within a very high concentrated oligopoly. Results from Data Envelopment Analysis (DEA) in 2010-2015 there were 1 efficient company. As a result of an oligopoly market structure is very tight, then in the telecommunications industry is a lot to make improvements to network sharing and speed the delivery of messages, telephone, and internet as well as to achieve efficient company should refer to the telecommunications industry, which reached the maximum efficient level. In order to achieve an efficient level that has not been efficient, the company must conduct debt reduction, labor usage more efficient and increase product sales.